A COMPARATIVE STUDY OF THE EFFECT OF TWO TRAINING PROGRAMS ACCORDING TO THE CROSSFIT AND TABATA METHODS IN DEVELOPING SOME FUNCTIONAL AND BIOCHEMICAL VARIABLES FOR FEMALE FOOTBALL PLAYERS - Saif Rasheed Ghanim; Maysa Khaled Ahmed; Alaa Jassim Mohammed (Proximus Journal Publishing, 2025)
The aim of the research is to identify the effect of Tabata training and CrossFit training in developing some functional and biochemical variables for female football players. The study was conducted on Solaf Sports Club players registered with the Federation for the 2022/2023 sports season, aged (23.15 ± 6.35) years, weighing (77.08 ± 3.74) kg, and with a height of (178.12 ± 8.85) cm, totaling (24) players. They were distributed into two experimental groups with (12) players for each group. The first experimental group implemented Tabata training, while the second experimental group implemented CrossFit training. The two training programs were implemented on the study sample, where the duration of the implementation of the two programs was (12) weeks, with (3) training units per week, the duration of each training unit was (90) minutes, where the total number of units was (36) training units. The researchers used the (T-TEST) law for independent and independent samples to find out the difference between the pre-test and post-test and the post-test for both groups. It was concluded that both training methods made a noticeable development in the study variables, and there was a relative superiority of CrossFit training in improving functional and biochemical variables, indicating its effectiveness in improving aerobic and anaerobic performance, as well as supporting physical endurance and increasing physiological values associated with athletic performance.
Keywords: Tabata training; CrossFit training; functional variables